Discourse of Apology and Plea in R&B Lyrics: A Pragmatic Analysis of “On Bended Knee” - Mutiara Salsabila Nuzula; Otong Setiawan Djauhari (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study explores the pragmatic dimensions of apology and emotional plea in the lyrics of Boyz II Men's “On Bended Knee”. As an emblematic R&B song from the 1990s, the lyrics are rich in expressive speech acts that convey regret, longing, and emotional vulnerability. The objective of this study is to analyze the types and functions of speech acts, particularly focusing on apology and pleading expressions using the framework of speech act theory and politeness strategies proposed by Brown and Levinson. This research applies a qualitative descriptive method with textual analysis as the main tool. The results indicate that the lyrics contain multiple expressive and commissive acts, such as requests, promises, and repeated apologies, demonstrating a strong emotional appeal. These elements construct a discourse of emotional surrender and remorse, reflecting key features of interpersonal communication in popular music. The study contributes to the understanding of how language in music can perform social functions beyond aesthetic value, particularly in articulating relational dynamics and emotional expression.